Avipoxvirus detected in tumor-like lesions in a white-faced whistling duck (Dendrocygna viduata) - Juliana F.V. Braga; Rodrigo M. Couto; Marcelo C. Rodrigues; Roselene Ecco (Pesquisa Veterinária Brasileira, 2020)
ABSTRACT: Avipoxvirus is the etiological agent of the avian pox, a well-known disease of captive and wild birds, and it has been associated with tumor-like lesions in some avian species. A white-faced whistling duck (Dendrocygna viduata) raised in captivity was referred to a Veterinary Teaching Hospital in Northeast due to cutaneous nodules present in both wings. A few days after the clinical examination, the animal died naturally. Once submitted to necropsy, histopathological evaluation of the lesions revealed clusters of proliferating epithelial cells expanding toward the dermis. Some of these cells had round, well-defined, intracytoplasmic eosinophilic material suggestive of poxvirus inclusion (Bollinger bodies). PCR performed on the DNA extracted from tissue samples amplified a fragment of the 4b core protein gene (fpv167), which was purified and sequenced. This fragment of Avipoxvirus DNA present in these tumor-like lesions showed high genetic homology (100.0%) with other poxviruses detected in different avian species in several countries, but none of them were related to tumor-like lesions or squamous cell carcinoma. This is the first report of Avipoxvirus detected in tumor-like lesions of a white-faced whistling duck with phylogenetic analysis of the virus.